Od zapomnienia do przypomnienia: casus Andrzeja Panufnika - Bolesławska-Lewandowska, Beata (Res Facta Nova, 2025)
In July 1954, Andrzej Panufnik left Warsaw to make recordings for Swiss Radio and, instead of returning to his homeland, made his way to London, where he requested political asylum. In a statement to the British press, he wrote: ‘[In Poland] I was so exploited politically that I had neither time or the peace of mind necessary to my creative work. In consequence for the last four years, for the first time in my life I have found myself completely unable to compose’. As a consequence of his decision to emigrate, the propaganda machine of the Polish People’s Republic decided to erase the composer from the country’s musical life and from the consciousness of music lovers in Poland. How were the political mechanisms used during the communist era applied to officially “forgetting” an inconvenient artist’s work? How did the memory of him survive (albeit in a distorted form) and how was it subsequently restored? And also, what dangers are associated not only with the deliberate blurring of the memory of the composer, but also with the deliberate restoration of him to the national cultural canon? The author considers these questions, drawing on Paul Connerton’s typology of seven types of forgetting and Aleida Assmann’s research on memory, recalling also the decolonisation perspective and using her own long-standing research on the music and work of Andrzej Panufnik.